Review of "Posthümanizm: Kavram, Kuram, Bilim-Kurgu" - Seda Arıkan (Ideas: Journal of English Literary Studies)
This article reviews "Posthümanizm: Kavram, Kuram, Bilim-Kurgu," written by Başak Ağın and published Siyasal Kitabevi in 2020.